Detection and Characterization of Carbapenemase-Producing Escherichia coli and Klebsiella pneumoniae from Hospital Effluents of Ouagadougou, Burkina Faso - Alix Bénédicte Kagambèga; René Dembélé; Léa Bientz; Fatima M’Zali; Laure Mayonnove; Alassane Halawen Mohamed; Hiliassa Coulibaly; Nicolas Barro; Véronique Dubois (Antibiotics, 2023)
Hospital wastewater is a recognized reservoir for resistant Gram-negative bacteria. This study aimed to screen for carbapenemase-producing Escherichia coli and Klebsiella pneumoniae and their resistance determinants in two hospital effluents of Ouagadougou. Carbapenem-resistant E. coli and K. pneumoniae were selectively isolated from wastewater collected from two public hospitals in Ouagadougou, Burkina Faso. Bacterial species were identified via MALDI-TOF mass spectrometry. Carbapenemase production was studied phenotypically using antibiotic susceptibility testing via the disk diffusion method. The presence of carbapenemases was further characterized by PCR. A total of 14 E. coli (13.59%) and 19 K. pneumoniae (17.92%) carbapenemase-producing isolates were identified with different distributions. They were, respectively, blaNDM (71.43%), blaVIM (42.86%), blaIMP (28.57%), blaKPC (14.29%), blaOXA-48 (14.29%); and blaKPC (68.42%), blaNDM (68.42%), blaIMP (10.53%), blaVIM (10.53%), and blaOXA-48 (5.26%). In addition, eight (57.14%) E. coli and eleven (57.89%) K. pneumoniae isolates exhibited more than one carbapenemase, KPC and NDM being the most prevalent combination. Our results highlight the presence of clinically relevant carbapenemase-producing isolates in hospital effluents, suggesting their presence also in hospitals. Their spread into the environment via hospital effluents calls for intensive antimicrobial resistance (AMR) surveillance.